Methamphetamine Use During the First or Second Half of Pregnancy Worsens Cardiac Ischemic Injury in Adult Female Offspring - Chavva, H; Rorabaugh, B R (Physiological research, 2022)
There is growing evidence that methamphetamine use during pregnancy may produce detrimental cardiovascular effects in the adult offspring. Prior work demonstrated that chronic methamphetamine exposure throughout the gestational period causes adult female offspring to become hypersensitive to myocardial ischemic injury. The goal of the present study was to determine whether this methamphetamine-induced effect occurs early or late in the gestational period. Pregnant female rats were divided into 4 experimental groups. Groups 1 and 2 received subcutaneous injections of saline (group 1) or methamphetamine (5 mg/kg) (group 2) throughout the gestational period. Group 3 received methamphetamine injections on days 1-11 and saline on days 12-22, and group 4 received saline on days 1-11 and methamphetamine on days 12-22. Hearts were isolated from adult (8 weeks) female offspring and subjected to 30 min ischemia and 2 hours reperfusion on a Langendorff isolated heart apparatus. Contractile function was measured via an intraventricular balloon, and infarct size was measured by triphenyltetrazolium chloride staining. Infarcts were significantly larger in methamphetamine exposed offspring regardless of whether they had been exposed to methamphetamine during the first half or the second half of the gestational period. Prenatal exposure to methamphetamine had no effect on preischemic contractile function or postischemic recovery of contractile function. These data indicate that methamphetamine use during either the first half or second half of pregnancy increases susceptibility to myocardial infarction in adult female offspring. These data provide further evidence that prenatal exposure to methamphetamine may increase the risk of developing cardiovascular diseases during adulthood.
Keywords: srdce; potkani Sprague-Dawley; těhotenství; Rats, Sprague-Dawley; Humans; methamfetamin; zvířata; Rats; zpožděný efekt prenatální expozice; Heart Injuries; Heart; Methamphetamine; Myocardial Infarction; Prenatal Exposure Delayed Effects; krysa rodu Rattus; ženské pohlaví; poranění srdce; Animals; infarkt myokardu; lidé; Pregnancy; Female